Energy and Exergy Analyses of a Pyroelectric‐Based Solar Energy Harvesting System. Issue 12 (4th December 2015) - Sharma, Manish; Vaish, Rahul; Chauhan, Vishal Singh
Abstract: This study is concerned with energy and exergy analyses of a solar energy harvesting system based on the pyroelectric effect. The [Bi0.5 (Na0.94 K0.05 Li0.016 )0.5 ]0.95 Ba0.05 TiO3 (BNKLBT) ceramic was studied in present investigation using finite‐element analysis, and the power output was optimized for different load resistance and load capacitance values. The maximum power output obtained was 2.2 μW across a load resistance of 50 MΩ and a 4.7 μF load capacitor. Further exergy analysis was performed for the pyroelectric energy harvesting system. The maximum values for the electrical and thermal exergies obtained were 2.3 μW and 37 mW, respectively. Furthermore, the maximum obtained electrical and thermal exergy efficiencies were 0.00013 % and 11.16 %, respectively. Abstract : Exergy marks the spot: This study is concerned with energy and exergy analyses of a solar energy harvesting system based on the pyroelectric effect. The [Bi0.5 (Na0.94 K0.05 Li0.016 )0.5 ]0.95 Ba0.05 TiO3 (BNKLBT) ceramic is studied in present investigation using finite‐element analysis, and the power output is optimized for different load resistance and load capacitance values. These pyroelectric materials can be used in solar photovoltaic (PV) panels to improve their efficiency.